Development and validation of an analytical method by hplc-dad for quantification of warfarin sodium in an extemporaneous preparation (2013)
In this work was carried out the development and quantification of an analytical methodology for quantification of Warfarin Sodium in an extemporaneous suspension for hospital use. Evaluation of specificity was achieved against its excipients and degradation compounds. The selectivity was evaluated against the excipients and degradation compounds. Linearity studies were performed in a range of concentration between 0.05 to 0.15 mg/mL. Precision was evaluated in levels of repeatability and intermediate precision and accuracy in three concentration levels corresponding to the 75, 100 and 125%. The results show that the validation of the methodology is selective, linear, accurate and precise; therefore, it is reliable for use in the quantification of active warfarin sodium in the extemporaneous suspension.